The Effect of Organizational Culture and Work Environment on Job Satisfaction Through Work Ethic - Intan Maulida Rizaldy; Tuty Sariwulan; Nadya Fadillah (Yayasan Pendidikan Islam Akmalia, 2023)
This research aims to obtain valid knowledge regarding the influence of organizational culture and work environment on job satisfaction through work ethic at PT. X. The research method used is quantitative. The data analysis technique was carried out using the SEM (Structural Equation Modeling) approach using Smart PLS (Partial Least Square) software. The population is employees of PT. X. Based on the outside measurement of the model used as a measure of validity and reliability of indicators, which includes measurement of convergent validity, discriminant validity, extracted variance (AVE), composite reliability, and cronbach's alpha, it can be concluded that all indicators in this case research are valid . Based on the inner model measurements used in this research to measure the relationship between variables, organizational culture and work environment variables on job satisfaction have a strong influence of 91% and the influence of organizational culture and work environment variables on work ethic has a large influence. strong influence of 89%. It can be concluded that work ethic is able to mediate the influence between organizational culture and work environment on job satisfaction